2021
DOI: 10.1371/journal.pone.0253620
|View full text |Cite
|
Sign up to set email alerts
|

Temporal discounting in adolescents and adults with Tourette syndrome

Abstract: Tourette syndrome is a neurodevelopmental disorder associated with hyperactivity in dopaminergic networks. Dopaminergic hyperactivity in the basal ganglia has previously been linked to increased sensitivity to positive reinforcement and increases in choice impulsivity. In this study, we examine whether this extends to changes in temporal discounting, where impulsivity is operationalized as an increased preference for smaller-but-sooner over larger-but-later rewards. We assessed intertemporal choice in two stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 84 publications
(117 reference statements)
2
3
0
Order By: Relevance
“…To address this concern, we conducted additional analyses after excluding food and monetary trials with payoffs occurring after 6 and 12 months. Although these supplementary analyses confirmed the results of previous studies ( Schüller et al, 2021 ) and our results obtained from the complete dataset, it remains uncertain whether participant behavior would have differed, had they been confronted with individually tailored food items and more realistic prices. Especially for highly delayed rewards, higher-priced food is more likely to be discounted than lower-priced food.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…To address this concern, we conducted additional analyses after excluding food and monetary trials with payoffs occurring after 6 and 12 months. Although these supplementary analyses confirmed the results of previous studies ( Schüller et al, 2021 ) and our results obtained from the complete dataset, it remains uncertain whether participant behavior would have differed, had they been confronted with individually tailored food items and more realistic prices. Especially for highly delayed rewards, higher-priced food is more likely to be discounted than lower-priced food.…”
Section: Discussionsupporting
confidence: 83%
“…These findings underscore the importance of considering scaling of individual differences in time insensitivity/sensitivity to reliably capture superior features of discounting behavior with Bayesian modeling ( Ebert and Prelec, 2007 ). Schüller et al (2021) have chosen a comparable approach and found that discounting money over shorter delays (up to 6 months compared with 1 year in our study) is also better captured by exponential as compared with hyperbolic discounting, which supports the validity of our findings even though our task included exceptionally long delays (e.g., 6 and 12 months). Despite convincing results of our model comparison, the parameter recovery of the winning model was only successful for k , as a measure of impulsivity, but not s, a factor of time sensitivity.…”
Section: Discussionsupporting
confidence: 82%
“…Abnormal reward processing, in particular, greater reward sensitivity, has been suggested to be a behavioural marker of TD [ 1 ]. However, only two studies previously investigated delay discounting of reward in TD, using a task similar to that used in the present study, also showing steeper reward discounting, but only for large rewards and only for adolescents suffering from TD [ 9 , 10 ]. In addition, as one of the previous study, we reported no significant effect of ADHD or OCD co-morbidities [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, only two studies previously investigated delay discounting of reward in TD, using a task similar to that used in the present study, also showing steeper reward discounting, but only for large rewards and only for adolescents suffering from TD [ 9 , 10 ]. In addition, as one of the previous study, we reported no significant effect of ADHD or OCD co-morbidities [ 10 ]. However, we found that connectivity between the right pre-SMA and the ventral striatum was related to both delay discounting and attentional impulsivity assessed with the BIS-11.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation